Distintas racionalidades sobre preservação ambiental: estudo de caso nos processos judiciais relativos à (não) abertura da estrada do Colono (1986-2020), no Parque Nacional do Iguaçu, Paraná - Franco, Caroline da Rocha (2023)
The overall objective of the research was to analyze the distinct rationales of environmental preservation and development in situations of environmental conflict litigation. To do só, a case study was conducted, in which the judicial process related to the Colono Road was analyzed – which proceeded between 1986 and 2020. The road is a 17.5 km stretch located within the Iguaçu National Park (INP), which is a full protection Conservation Unit, according to Law No. 9,985/2000. The research is applied and qualitative, with exploratory analysis through bibliographic research and documentary investigation, in addition to using primary and secondary data, along with the analysis of judicial processes related to the opening/closure of the Colono Road. The strategy used is a case study, with content analysis supported by the Atlas.ti software. Through the case study conducted in the thesis, several themes were reflected upon: (i) the history of the region’s occupation; (ii) argumentative strategies, interests, and disputes; (iii) the judicialization of environmental conflicts; (iv) the flexibility of environmental policies. The thesis hypothesis was confirmed because the judicialized environmental conflict in question regarding the Colono Road is not limited to regional interests; it reflects on the national system of conservation units (SNUC), not only because it intends to create a new category called ‘road-park.’ Opening a road within one of the country’s largest national parks would weaken the entire environmental protection system. This would certainly have repercussions on other National Parks, as it represents the removal of their full protection status. It was evident that the closure of the Colono Road was a measure taken by a judicial injunction, without any discussion with the population that used this road as a means of integration with other regions of the country and the state. This generated dissatisfaction among the population, which had struggled to build access to the region. Regarding the judicialization of environmental policies, it is noted that the issue is controversial, as it creates an overload of work for the judiciary and can also be seen as a democratic deficit, considering that judges are not elected by the people, unlike the legislative and executive branches. It is recommended that in the case of environmental litigation, the judiciary, instead of receiving the demand and processing it as a common civil dispute (in which lawyers and experts file petitions), should require open debates, such as public hearings or environmental forums. It was evident that over the thirty years in which the process proceeded, the economic importance of the road was not demonstrated, although it is recognized that the agenda mobilized and brought together the community around the Park. Thus, it seems that only very specific private interests would benefit from a possible reopening of the Colono Road. Finally, from the environmental conflict that was brought into legal terms, argumentative schemes were extracted, demonstrating the different rationales for the appropriation of natural resources. In them, it is possible to see the main discourses of each group of stakeholders involved in the conflict.